Student Knowledge, Skills, and Self-Efficacy Gains After Completing an Advanced Pharmacy Practice Experience in Geriatrics - Donohoe, Krista L. (Am J Pharm Educ, 2016)
Objective. To assess changes in pharmacy students’ knowledge, skills, and self-efficacy after completing an advanced pharmacy practice experience (APPE) in geriatrics. Design. During the 2013-2014 academic year, 30 Virginia Commonwealth University (VCU) School of Pharmacy students were required to complete a 5-week Geriatrics APPE at Plaza Professional Pharmacy in Richmond, Virginia. All students completed a 25-point knowledge-based pre- and post-assessment to measure students’ self-efficacy. The average time required to accurately fill one unit dose prescription card before and after completing the APPE was also evaluated. Assessment. Students’ average score on the knowledge component improved significantly from 54% to 88% after completing the APPE. The average time required to fill one prescription decreased significantly from 4.0 minutes to 2.5 minutes. Students reported an increase in self-efficacy in the following areas: communication, immunizations, geriatrics-specific pharmacotherapy knowledge, and the ability to fill and check monthly unit dose prescription cards. Conclusion. Requiring fourth-year pharmacy students to complete a geriatrics APPE as a capstone experience to the integrated geriatrics content covered in the first through third years of the doctor of pharmacy (PharmD) curriculum provides an important opportunity to improve students’ knowledge, skills, and self-efficacy in providing care to older adults.